L1CAM variants cause two distinct imaging phenotypes on fetal MRI. Issue 10 (12th September 2021) - Accogli, Andrea; Goergen, Stacy; Izzo, Giana; Mankad, Kshitij; Krajden Haratz, Karina; Parazzini, Cecilia; Fahey, Michael; Menzies, Lara; Baptista, Julia; Carpineta, Lucia; Tortora, Domenico; Fulcheri, Ezio; et al.
Abstract: Data on fetal MRI in L1 syndrome are scarce with relevant implications for parental counseling and surgical planning. We identified two fetal MR imaging patterns in 10 fetuses harboring L1CAM mutations: the first, observed in 9 fetuses was characterized by callosal anomalies, diencephalosynapsis, and a distinct brainstem malformation with diencephalic–mesencephalic junction dysplasia and brainstem kinking. Cerebellar vermis hypoplasia, aqueductal stenosis, obstructive hydrocephalus, and pontine hypoplasia were variably associated. The second pattern observed in one fetus was characterized by callosal dysgenesis, reduced white matter, and pontine hypoplasia. The identification of these features should alert clinicians to offer a prenatal L1CAM testing.